Streptococcal infection in childhood Henoch-Schönlein purpura: a 5-year retrospective study from a single tertiary medical center in China, 2015-2019 - Guo Zhen Fan; Rui Xue Li; Qi Jiang; Man Man Niu; Zhen Qiu; Wei Xia Chen; Hui Hui Liu; Jin Wei Ruan; Peng Hu (BMC, 2021)
Abstract Background The present study focuses on the associations of streptococcal infection with the clinical phenotypes, relapse/recurrence and renal involvement in Henoch-Schönlein purpura (HSP) children. Methods Two thousand seventy-four Chinese children with HSP were recruited from January 2015 to December 2019. Patients' histories associated with HSP onset were obtained by interviews and questionnaires. Laboratory data of urine tests, blood sample and infectious agents were collected. Renal biopsy was performed by the percutaneous technique. Results (1) Streptococcal infection was identified in 393 (18.9%) HSP patients, and served as the most frequent infectious trigger. (2) Among the 393 cases with streptococcal infection, 43.0% of them had arthritis/arthralgia, 32.1% had abdominal pain and 29.3% had renal involvement. (3) 26.1% of HSP patients relapsed or recurred more than 1 time within a 5-year observational period, and the relapse/recurrence rate in streptococcal infectious group was subjected to a 0.4-fold decrease as compared with the non-infectious group. (4) No significant differences in renal pathological damage were identified among the streptococcal infectious group, the other infectious group and the non-infectious group. Conclusions Streptococcal infection is the most frequent trigger for childhood HSP and does not aggravate renal pathological damage; the possible elimination of streptococcal infection helps relieve the relapse/recurrence of HSP.